Mensiasati Ideologi Neoliberal dalam Pendidikan - Ilyya Muhsin (Universitas Islam Indonesia, 2008)
When globalization put in education, cultural and economic, it was expansion to instile western ideology and brain washing for people in the underdeveloping countries like indonesai. Ironically, the goverment legitimed foreign higher education in Indonesia. There was dillemating choice that the present of foreign higher education in Indonesia, at the one hand make education more competitive riching quality, and the other hand, occure an indoctrination of ideology neoliberalism. Western life standart to be the complete opposite of produce civilization in the nation without balancing of local culture must be permanent. This article trais to discuse the fight of westren ideology wich developing in education, exacly for currents issues. Kata Kunci: Komersialisasi Pendidikan, Perguruan Tinggi Asing, Globalisasi